Constructing single‐atom Ni on N‐doped carbon via chelation‐anchored strategy for the hydrogenolysis of lignin. Issue 2 (31st August 2022) - Li, Tianjin; Chen, Bo; Cao, Meifang; Ouyang, Xinping; Qiu, Xueqing; Li, Changzhi
Abstract: The efficient utilization of lignin remains a great challenge due to its complex nonrepetitive structure and the lack of efficient catalyst. Herein, a single‐atom catalyst Ni@N‐C was designed via a facile chelation‐anchored strategy. Ni atoms were immobilized on the N‐doped carbon carrier by a two‐stage pyrolysis of a mixture of d ‐glucosamine hydrochloride, nickel acetate, and melamine. d ‐glucosamine hydrochloride as a chelating agent prevented the aggregation of Ni 2+, and melamine provided enough N to anchor Ni by forming Ni–N4 structure. Ni@N‐C gave a 31.2% yield of aromatic compounds from lignin hydrogenolysis, which was twice higher than that achieved by Ni cluster catalyst. Based on the experimental and density functional theory (DFT) calculation results, the higher activity of Ni@N‐C was attributed to its lower H2 dissociation energy and the reduced energy barriers of the transition states. The strategy described opens an efficient green avenue for preparing single‐atom catalyst that possesses outstanding activity in lignin depolymerization.